2023
DOI: 10.3390/f14051044
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Nitric Acid Rain Aggravated the C and P Limits of Forest Soil Microorganisms

Abstract: With the comprehensive emissions of fossil fuel combustion and transportation waste gas, the concentrations of nitrogen oxides (NOX) in the environmental atmosphere increase significantly, leading to nitric acid rain (NAR) pollution. However, the effects of NAR on soil enzyme activities and soil microbial metabolism are unclear. In this study, the Quercus acutissima Carruth. forest in the Yangtze River Delta of China was selected as the experimental subject, and was exposed to the simulated spraying of NAR wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…EEA stoichiometric ratios reflect soil microbial nutrient acquisition and limitation status [9]. Numerous studies have investigated forest EEA and its stoichiometry [16,21,[36][37][38]. In our study, soil microbes were co-limited by C and P (Figure 3).…”
Section: Nutrient Limitation Status Of Soil Microbesmentioning
confidence: 69%
“…EEA stoichiometric ratios reflect soil microbial nutrient acquisition and limitation status [9]. Numerous studies have investigated forest EEA and its stoichiometry [16,21,[36][37][38]. In our study, soil microbes were co-limited by C and P (Figure 3).…”
Section: Nutrient Limitation Status Of Soil Microbesmentioning
confidence: 69%
“…Microbial community structure can reflect the quality and health of soil to a certain extent, which is of great value in exploring the functional characteristics of soil and the structural properties of the ecosystem [9]. Previous studies have shown that AR can lead to soil acidification [10][11][12], which can promote an increase in the concentration of hydrogen ions in soil and cause changes in the composition and structure of soil microbial communities [13]. In addition, soil microbial diversity in farmland soil is closely related to soil quality [14].…”
Section: Introductionmentioning
confidence: 99%